DIVERSITY OF MANGROVES AND ASSOCIATED PLANTS IN MANDANGISIAO ESTUARY, MISAMIS ORIENTAL, PHILIPPINES - SITOY, WELLA BABE O.; BUENAVISTA, DAVE P. (Research Center for Biology, 2024)
The study aimed to assess the diversity status of mangroves and associates. Four transect lines were established perpendicular to the shoreline, ranging from 20 to 100 meters based on mangrove stand size. Along these transects, three 10 m × 10 m quadrat plots were set up to evaluate mangrove trees, and within each quadrat, a 2 m × 2 m regeneration plot was established. The study calculated the di-versity indices, such as relative frequency, relative density, and relative dominance to determine the species im-portance value. A total of four mangrove species and two associated plants were identified, representing three mangrove families and three genera, as well as three plant families and three genera for associated plants. The record-ed species included Avicennia marina, Nypa fruticans, Rhizophora mucronata, Sonneratia caseolaris, Acanthus ebrac-teatus, and Acrostichum speciosum. The overall diversity value of the mangroves and associated plants was 0.87, indi-cating relatively low species richness. The true mangroves, Rhizophora mucronata exhibited the highest values for relative density (68.07%), while Nypa fruticans is the highest in terms of relative dominance (42.20%). Both have the same highest value in relative frequency (32.43%). All in all, the highest species importance value for true mangroves is Rhizophora mucronata with 126.23%. In associated plants, highest value of relative density and relative frequency belongs to Acanthus ebracteatus with 58% and 60%, respectively. Subsequently, the highest species importance value for associated plants is 118% for Acanthus ebracteatus. The study concluded that the Mandangisiao Estuary in Jasaan, Misamis Oriental has a limited species diversity, contrary to the initial hypothesis. Furthermore, the mangrove forest in the estuary faces potential threats from garbage dumping, tree cutting, boat mooring, and human encroachment, despite all the recorded species having a Least Concern conservation status.